Biomimetic Magnetic Particles for the Removal of Gram-Positive Bacteria and Lipoteichoic Acid. - Friedrich, Bernhard; Eichermüller, Julia; Bogdan, Christian; Cunningham, Sarah; Hackstein, Holger; Strauss, Richard; Alexiou, Christoph; Lyer, Stefan; Tietze, Rainer (Pharmaceutics, 2022)
Gram+ bacteria are very common in clinical medicine and responsible for a large number of infectious diseases. For example, Gram+ bacteria play a major role in causing bloodstream infections and sepsis. Therefore, the detection of Gram+ bacteria is of great importance for the diagnosis and treatment of infectious diseases. Furthermore, these bacteria are often present in biofilms that cover implants. Recent research work has mainly focused on the biologic activity and removal of Gram-negative bacteria or bacterial components such as lipopolysaccharides (LPS). In contrast, the effects of lipoteichoic acid (LTA) have been less well studied so the relevance of their removal from body fluids is possibly underestimated. To address this topic, we evaluated superparamagnetic iron oxide particles (SPION) carrying different peptides derived from the innate immune receptor (GP-340) for their ability to bind and remove Gram+ bacteria and LTA from different media. Our results show that, beyond S. aureus, effective agglutinating and removing of S. pneumoniae was possible. Furthermore, we were able to show for the first time that this was possible with LTA alone and that the magnetic removal of bacteria was also efficient under flow conditions. We also found that this method was able to capture Stapyhylococcus aureus from platelet concentrates, which can help to enhance the sensitivity of microbiological diagnostics, quality control measures, and blood product safety.
EVALuna2:508460